2016
DOI: 10.1007/s10753-016-0391-6
|View full text |Cite
|
Sign up to set email alerts
|

Coptisine Prevented IL-β-Induced Expression of Inflammatory Mediators in Chondrocytes

Abstract: Interleukin 1β (IL-1β) is a pleiotropic pro-inflammatory cytokine that plays a critical role in the development of osteoarthritis (OA). Coptisine is an isoquinoline alkaloid extracted from Coptidis rhizome and has been reported to possess anti-inflammatory activity. However, the anti-inflammatory effects of coptisine on interleukin-1 beta (IL-1β)-stimulated chondrocytes have not been reported. Therefore, the aim of this study was to investigate the effects of coptisine on IL-1β-induced inflammation in human ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…According to several reports, IL-1β-stimulated expression of MMPs is associated with the suppression of the NF-κB signaling pathway [36373839]. Jung and his colleagues reported that Schisandrae Fructus, an anti-inflammatory medicinal plant used in folk medicine, inhibited IL-1β-induced expression and activity of MMP-1, MMP-3, and MMP-13 and markedly suppressed the nuclear translocation of NF-κB by blocking IkB-alpha degradation in SW1353 human chondrocytes [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to several reports, IL-1β-stimulated expression of MMPs is associated with the suppression of the NF-κB signaling pathway [36373839]. Jung and his colleagues reported that Schisandrae Fructus, an anti-inflammatory medicinal plant used in folk medicine, inhibited IL-1β-induced expression and activity of MMP-1, MMP-3, and MMP-13 and markedly suppressed the nuclear translocation of NF-κB by blocking IkB-alpha degradation in SW1353 human chondrocytes [36].…”
Section: Discussionmentioning
confidence: 99%
“…Another natural product, matrine, inhibited IL-1β-induced expression of MMPs by suppressing the activation NF-κB in human chondrocytes in vitro [38]. Zhou et al reported that coptisine, an isoquinoline alkaloid extracted from an antiinflammatory medicinal plant, also inhibited the expression of MMP-3 and MMP-13 through inhibition of NF-κB activation in human chondrocytes [39]. …”
Section: Discussionmentioning
confidence: 99%
“…As claimed by several reports, IL-1β-stimulated expression of MMPs is associated with the suppression of the NF-κB signaling pathway [36373839]. It was reported that coptisine, an isoquinoline alkaloid extracted from an anti-inflammatory medicinal plant, also inhibited the expression of MMP-3 and MMP-13 through inhibition of NF-κB activation in human chondrocytes [36].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that coptisine, an isoquinoline alkaloid extracted from an anti-inflammatory medicinal plant, also inhibited the expression of MMP-3 and MMP-13 through inhibition of NF-κB activation in human chondrocytes [36]. Another natural product, matrine, inhibited IL-1β-induced expression of MMPs by suppressing the activation NF-κB in human chondrocytes in vitro [37].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological study confirmed that magnoflorine could regulate the differentiation of neutrophils and T cells for anti-inflammation [45]. Coptisine and calycosin could modulate the activation of the nuclear factor-κB (NF-κB), MAPK or PI3K/Akt/GSK-3 signaling pathways, contributing to an inhibitory effect on the inflammatory response induced by pro-inflammatory cytokines [46, 47]. Jatrorrhizine [47], berberine [48] and palmatine [49] have inhibitory functions on cell apoptosis through anti-oxidative activation or intervening in the inducible nitric monoxide synthase system.…”
Section: Discussionmentioning
confidence: 99%